Tuberculosis knowledge and attitude among non-health science university students needs attention: a cross-sectional study in three Ethiopian universities - Abiyu Mekonnen; Jeffery M. Collins; Eveline Klinkenberg; Dawit Assefa; Abraham Aseffa; Gobena Ameni; Beyene Petros (BMC, 2020)
Abstract Background Ethiopia is among the 14 high TB, TB/HIV and MDR-TB burden countries globally. Prior studies indicate students attending universities in Ethiopia may be at increased risk for active tuberculosis (TB) relative to the general population, mainly due to the dramatic increase in expansion of the enrollment scale of universities.This study sought to gain insight about non-health science university students' TB knowledge and attitudes to help develop a strategy for TB education in this population. Methods A cross-sectional study was conducted from October to December 2018 among non-health science university students at three eastern Ethiopia public universities. Participants were considered having 'good' knowledge on TB when they correctly mentioned the communicability, means of transmission and prevention methods of TB and recognized modern medicine as the best treatment for TB. Participants were considered as having 'acceptable' attitude towards TB when they indicated they would seek immediate care for TB diagnosis, not hide a TB diagnosis and feel compassion to help people with TB. Results A total of 1720 non-health science university students participated. Only 614 (35.7%) of the students had 'good' knowledge on TB. This differed significantly between universities, with students from Haramaya and Dire Dawa universities more likely to have 'good' TB knowledge than their counterparts from Jigjiga University [COR (Crude Odds Ratio):1.62 and 1.94, respectively; and 95% Confidence Interval (CI): (1.236, 2.079) and (1.511, 2.483), respectively]. Only a third of students, 555 (32.3%) mentioned 'bacteria' as causing TB, and 836 students (48.6%) had ever heard of Multi Drug Resistant-TB (MDR-TB). An 'acceptable' attitude towards people with TB was observed in 666 students (38.7%). Even though 739 students (43%) felt compassion and desire to help TB patients, 213 (12%) and 382 (22%) mentioned they fear and tend to stay away from TB patients, respectively. Conclusions The present study revealed that non-health science university students lack important TB knowledge and have misconceptions about TB in eastern Ethiopia. University administrators and other stakeholders striving against TB should provide due attention to university settings and consider development of student education programs to improve awareness and knowledge of TB disease.